Nuclear Deterrence in the Twentieth Century : the Impact of Atomic Weapons on Conflict between Interstate Dyads. - Pasley, James F. (Edwin Mellen Press, 2010)
This work offers both qualitative and quantitative analyses of how the presence of nuclear weapons effects conflict escalation rates among international states. The qualitative section of the book focuses on the volatile Indo-Pakistani relationship and clearly demonstrates that the addition of nuclear weapons has served to retard conflict escalation between the two.